(untitled) (KULT_online, 2010)
The articles in Archiv – Macht – Wissen (Archive – Power – Knowledge) focus from different temporal and regional perspectives on the variety of possible archive constructions that try to make obsolete the well-established images of the archive as a static, unvarying place. They could be read as first research results of the homonymous research training group of the University of Bielefeld. The variety of papers, mostly presented by historians, ranges from French late mediaeval royal archives, to modern cultural transfers between Europe and China, to postcolonial archive critics. They all reflect the conditions of the formation of archives and their collections as well as power-relations as a basic condition of historical tradition.